Clinical and metabolic response to probiotic supplementation in patients with rheumatoid arthritis: a randomized, double‐blind, placebo‐controlled trial. (2nd May 2016) - Zamani, Batol; Golkar, Hamid R.; Farshbaf, Shima; Emadi‐Baygi, Modjtaba; Tajabadi‐Ebrahimi, Maryam; Jafari, Parvaneh; Akhavan, Reyhaneh; Taghizadeh, Mohsen; Memarzadeh, Mohammad R.; Asemi, Zatollah
Abstract: Objective: This study was performed to determine the effects of probiotic supplementation on clinical and metabolic status of patients with rheumatoid arthritis (RA). Methods: Sixty patients with RA aged 25–70 years were assigned into two groups to receive either probiotic capsules ( n = 30) or placebo ( n = 30) in this randomized, double‐blind, placebo‐controlled trial. The patients in the probiotic group received a daily capsule that contained three viable and freeze‐dried strains: Lactobacillus acidophilus (2 × 10 9 colony‐forming units [CFU]/g), Lactobacillus casei (2 × 10 9 CFU/g) and Bifidobacterium bifidum (2 × 10 9 CFU/g) for 8 weeks. The placebo group took capsules filled with cellulose for the same time period. Fasting blood samples were taken at the beginning and the end of the study to quantify related markers. Results: After 8 weeks of intervention, compared with the placebo, probiotic supplementation resulted in improved Disease Activity Score of 28 joints (DAS‐28) (−0.3 ± 0.4 vs . −0.1 ± 0.4, P = 0.01). In addition, a significant decrease in serum insulin levels (−2.0 ± 4.3 vs . +0.5 ± 4.9 μIU/mL, P = 0.03), homeostatic model assessment‐B cell function (HOMA‐B) (−7.5 ± 18.0 vs . +4.3 ± 25.0, P = 0.03) and serum high‐sensitivity C‐reactive protein (hs‐CRP) concentrations (−6.66 ± 2.56 vs . +3.07 ± 5.53 mg/L, P < 0.001) following the supplementation of probiotics compared with the placebo. Subjects who received probiotic capsules experienced borderline statistically significant improvement in total‐ ( P = 0.09) and low‐density lipoprotein‐cholesterol levels ( P = 0.07) compared with the placebo. Conclusion: Overall, the results of this study indicated that taking probiotic supplements for 8 weeks among patients with RA had beneficial effects on DAS‐28, insulin levels, HOMA‐B and hs‐CRP levels.